Negros e indígenas cotistas da Universidade Estadual de Mato Grosso do Sul: desempenho acadêmico do ingresso à conclusão de curso - Cordeiro, Maria José de Jesus Alves (2008)
Brazil has an image of a tolerant and democratic nation that doesn't practice racial segregation. The ideology of miscegenation has been reproduced through repetition, generation after generation, using mainly the education system as vehicle, and the curriculum. The affirmative actions, in this case the policy of quotas, are questioning that image and making Brazilians think more critically about ethnic and racial justice and equity. The quotas are considered instruments for repairing, compensation and sociocultural inclusion. At UEMS, the quotas were established by the Law no. 2.589, of December 26, 2002, that reserves vacancies for indigenes and the Law no. 2.605, of January 6, 2003, that reserves 20% of the vacancies for blacks. They were regulated after debate with leaderships of the black movement, indigenes and the academic community. To follow up and evaluate the process of their implementation and their results, as the responsible manager for their implantation in UEMS, I accomplished this research as thesis of my doctorate in Education-Curriculum at PUC/SP, aiming to identify and to analyze to what or whom is attributed the success or academic failure of the students admitted in the quota system, from their admittance to graduation. It´s a qualitative research, that uses the case study methodology, but also quantitative data. Thirty seven (37) courses of the university were focus of the investigation. I analyzed and compared the performance of whites, blacks and indigenes from their admittance tests on December 2003, 2004, 2005 and 2006, to the final averages of their school years of 2004, 2005, 2006 and 2007, when the first students under the quota system concluded the four year courses. There were also applied questionnaires to identify the profile of those students. The results demonstrate that there isn t any significant difference between white and black students' academic performance under quota system. That conclusion disassembles the nucl